KEEFEKTIFAN MODEL PEMBELAJARAN INKUIRI MELALUI PERCOBAAN SEDERHANA TERHADAP HASIL BELAJAR IPAS SISWA KELAS IV SD NEGERI SIDOMULYO 01 PATI - Salsa Anica Septaningtias; Wijayanti, Arfilia; Mudzanatun (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study was to determine the effectiveness of the inquiry learning model through simple experiments on the learning outcomes of Science and Social Sciences (IPAS) in fourth-grade students at SD Negeri Sidomulyo 01 Pati. This study used a quantitative approach with One-Group Pretest-Posttest Design. The sample consisted of 17 students. The results showed a significant increase in cognitive learning outcomes, where the pretest mean of 43.53 rose to 79.06 in the posttest, and classical mastery increased from 5.88% to 94.11%. The t-test analysis showed thitung (13.06) > ttabel (2.120). Significant effectiveness was also found in the affective aspect with an average score of 83.00 (Good category) and classical mastery of 82%. The psychomotor aspect showed an average score of 88.95 (Very Good category) with 100% classical mastery. Thus, the inquiry model through simple experiments is effective in improving cognitive, affective, and psychomotor learning outcomes.